Co-occurrence Interaction Networks of Extremophile Species Living in a Copper Mining Tailing - Galvez, Gabriel; Ortega, Jaime; Fredericksen, Fernanda; Aliaga-Tobar, Victor; Parra, Valentina; Reyes-Jara, Angélica; Pizarro, Lorena; Latorre, Mauricio (Frontiers in Microbiology, 2022)
Copper mining tailings are characterized by high concentrations of heavy metals and an acidic pH, conditions that require an extreme adaptation for any organism. Currently, several bacterial species have been isolated and characterized from mining environments; however, very little is known about the structure of microbial communities and how their members interact with each other under the extreme conditions where they live. This work generates a co-occurrence network, representing the bacterial soil community from the Cauquenes copper tailing, which is the largest copper waste deposit worldwide. A representative sampling of six zones from the Cauquenes tailing was carried out to determine pH, heavy metal concentration, total DNA extraction, and subsequent assignment of OTUs. According to the elemental concentrations and pH, the six zones could be grouped into two sectors: i) the “new tailing”, characterized by neutral pH and low concentration of elements, and ii) the “old tailing”, having extremely low pH (~3.5) and a high concentration of heavy metals (mainly copper). Even though the abundance and diversity of species were low in both sectors, the Pseudomonadaceae and Flavobacteriaceae families were over-represented. Additionally, the OTU identifications allowed us to identify a series of bacterial species with diverse biotechnological potentials, such as copper bioleaching and drought stress alleviation in plants. Using the OTU information as a template, we generated co-occurrence networks for the old and new tailings. The resulting models revealed a rearrangement between the interactions of members living in the old and new tailings, and highlighted conserved bacterial drivers as key nodes, with positive interactions in the network of the old tailings, compared to the new tailings. These results provide insights into the structure of the soil bacterial communities growing under extreme environmental conditions in mines.